Stress in the Workplace, Depression, and Academic Workloads of Public School Teachers - Dominado, Noel L.; Valdez, Lilia G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Stress and depression are unavoidable in the workplace and have turn out to be a perennial have fascinated many researcher in modern eras. The current study aims to findings the relationship between demographic profile, stress, and depression in the workplace. A descriptive sequential explanatory research design was used. A questionnaire was adopted from the American Institute of stress (2011) and Depression organization New Zealand (n.d.), the open-ended question on academic workloads, and coping mechanism as the whole main instruments used to gather the data for the current study. A total of 100 public school teachers were randomly selected from 7 clusters in the Division of Pampanga – Philippines. The result showed that the majority of the respondents were between the ages 32-37 years old, 53% of them were male, 84% were junior high school teachers, and 26% had been serving four to seven years, the stress grand mean 2.13 which means they were disagreeing, a total score of 63% of the respondents was moderately well, the depression grand mean was 1.76 with a descriptive rating of several days, a total score of 57.6% of the respondents moderately well, but things may get worse. It is also revealed that there is no significant as to sex, depression, stress, teaching level, and educational attainment. While the age, depression, sex, stress, teaching level, depression, educational attainment, years in service to stress, depression stating that there is a highly significant.